2004
DOI: 10.1038/sj.ijo.0802721
|View full text |Cite
|
Sign up to set email alerts
|

Weight change and cognitive performance

Abstract: METHODS:The predictive power of the annual change in BMI with cognitive performance was investigated by a binary logistic regression analysis (backward) using sex, age, BMI 1990, BMI 2000, diastolic blood pressure, diabetes status, and optimal health status as additional predictors. RESULTS: In the last step, the following variables remained in the model: annual change in BMI (quadratic term; Po0.01); ApoE genotype (Po0.05); and optimal health status (Po0.01). CONCLUSION: The association between the extent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
1
20
2
Order By: Relevance
“…Memory measures are sensitive to cognitive decline since early midlife [43] and are the best discriminators of presymptomatic dementia [44]. The life course trend observed for BMI and memory was also observed for verbal fluency, ostensibly consistent with previous findings [45], although the associations between BMI gain at every age and this outcome were explained by the covariates. The same trend was also found for the NART, which, as a measure of cognitive “reserve” [46], might have been expected to augment in those with lower BMI gain during earlier adulthood, and has not previously been investigated in this context.…”
Section: Discussionsupporting
confidence: 87%
“…Memory measures are sensitive to cognitive decline since early midlife [43] and are the best discriminators of presymptomatic dementia [44]. The life course trend observed for BMI and memory was also observed for verbal fluency, ostensibly consistent with previous findings [45], although the associations between BMI gain at every age and this outcome were explained by the covariates. The same trend was also found for the NART, which, as a measure of cognitive “reserve” [46], might have been expected to augment in those with lower BMI gain during earlier adulthood, and has not previously been investigated in this context.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast several prospective studies linked both low and high body weight, weight loss and weight gain to risk of AD (Nourhashemi et al 2002, 2003; Gustafson et al 2003; Bagger et al 2004; Brubacher et al 2004; Buchman et al 2005; Goble 2005; Jeong et al 2005; Kivipelto et al 2005; Razay and Vreugdenhil 2005; Rosengren et al 2005; Stewart et al 2005; Tabet 2005; Whitmer et al 2005a; Waldstein and Katzel 2006; Arbus et al 2008; Atti et al 2008). The strongest effect was in a meta-analysis associating obesity (assessed by high body mass index) and the risk of AD (odds ratio, OR, 1.59 95% CI 1.02–2.5; z = 2.0; p = .042) (Profenno et al 2009).…”
Section: Antecedent Risk Factors That Increase the Risk Of Alzheimer mentioning
confidence: 97%
“…Gunstad et al (2006) classified participants as normal, overweight, or obese and found significant memory impairments in a variety of memory tasks that correlated with BMI (and also not interacting with age). Other studies have used longitudinal analyses, however, results are mixed with some studies finding a relationship (Brubacher et al, 2004) and others finding no correlation (Cournot et al, 2006). Recent research further suggests that hippocampal neurogenesis may also be influenced by diet, insulin levels, and genetic factors (Brubacher et al, 2004; Lindqvist et al, 2006; Nichol et al, 2009; Wallner-Liebmann et al, 2010; Clark et al, 2011; Grillo et al, 2011).…”
Section: Working Out Your Body To Expand Your Mindmentioning
confidence: 99%
“…Other studies have used longitudinal analyses, however, results are mixed with some studies finding a relationship (Brubacher et al, 2004) and others finding no correlation (Cournot et al, 2006). Recent research further suggests that hippocampal neurogenesis may also be influenced by diet, insulin levels, and genetic factors (Brubacher et al, 2004; Lindqvist et al, 2006; Nichol et al, 2009; Wallner-Liebmann et al, 2010; Clark et al, 2011; Grillo et al, 2011). While these results are likely not enough to make you think twice about skipping on a run to watch TV, they do suggest that our mind and body may be more closely connected than previously thought—and extend the boundaries commonly applied to embodied cognition.…”
Section: Working Out Your Body To Expand Your Mindmentioning
confidence: 99%